Moomin The Treasure - Taylor, Mary (London : Lady Bird books, 2020)
I want to go on a trip," said Moomin. Moomin, Snorkmaiden, Moominmamma, Moominpappa and Little My look for treasure
Keywords: Juvenile works; Fiction